Motivasi Kerja Pegawai Di Kantor Keyahbandaran Utama Makassar - Muh Nasrullah; Rudi Salam; Dwi Pratiwi; Risma Niswaty (JURNAL ILMIAH MANAJEMEN & BISNIS, 2017)
This study aims to determine the motivation of employees at the Office Kesyahbandaran Utama Makassar. The type of research is descriptive, with population of all employees at Kesyahbandaran Utama Makassar Office amounting to 265 people / employees. Determination of samples as much as 20 percent with the technique of sampling by Proportionate Stratified Random Sampling, as many as 53 people. Data collection was done through observation technique, questionnaire, interview and documentation, while data analysis was done by percentage technique then interpreted descriptively. The result of the research shows that employee work motivation at Kesyahbandaran Utama Makassar Office is in high category, seen from maintenance factor and satisfaction factor with sub indicator of organization policy, good supervision, adequate compensation, work environment, job satisfaction, job performance, and responsibility.